Multifunctional Design Ratios for Calculating Power Losses and Energy Efficiency of Long-Distance Electricity Transmission - G. E. Pospelov; Т. G. Pospelova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents design ratios for calculating power losses, efficiency factor and its maximal value for a long-distance electricity transmission. Universality of these ratios with due account of electromagnetic wave propagation nature and intermediate connections and multifunctional application are considered in the paper. The ratios permit to construct algorithms while designing, pricing at wholesale electricity market and can be used in the training process.